Social Education of Early Marriage (Pre-Marriage Pregnancy in Gowa District, South Sulawesi) - Sam’un Mukramin; Halawatiah Halawatiah (SIMULACRA: JURNAL SOSIOLOGI, 2018)
Early marriage was underage marriage, one of the reasons for the occurrence of pre-marriage pregnancy in Indonesia. This research used descriptive qualitative method, with informants of early marriage, family of perpetrators, public figure and government agencies. Data collecting were using observation, interviews and documentation. The results of this study indicate that the factors causing the occurrence of early marriage due to: (i) the influence of promiscuity (dating); (ii). the influence of the development of information technology (internet and mass media); (iii). poor parental and community supervision; (iv). the availability of the affordable lodging facilities; (v) lack of adolescent religious understanding. Pre-marriage pregnancy is done through: (i). official marriage; (ii). the unacknowledged marriage of law or siri’; (iii). the process of eloping; and (iv). the contractual agreement between the parents.